Transmission and processing for data center networking - Binh, Le Nguyen (IOP ebooks. 2020 collection., 2020)
This book offers insights into transport technology for data centres and the principal techniques for modern communication transmission of ultra-wideband channels. The book begins with an introduction to digital transmission technologies and data centre networking, progressing to discussions on access and DC networking transmission technologies and super-channel transmission by multi-carrier sources, before concluding with a chapter on photonic signal processors. The comprehensive and up-to-date overview offered by the book is an invaluable source for scientists, engineers, professors and mid-senior level students involved with data transmission and processing. Part of IOP Series in Advances in Optics, Photonics and Optoelectronics.